Fifth grade, here comes trouble - McKenna, Colleen O'Shaughnessy. (New York : Scholastic., 1989)
Unlike the other girls in her class, Collette Murphy becomes worried and embarrassed when she is invited to her first boy/girl party.
M
b
b
Keywords: Parties -- Fiction; Schools -- Fiction